2010
DOI: 10.4103/0970-2113.68309
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in the Kashmir valley

Abstract: Background:Lung cancer has been found to be the second commonest cancer according to a hospital-based data from Kashmir, India. However, no incidence studies are available.Objective:To ascertain the incidence of lung cancer in Kashmir.Materials and Methods:All newly histologically diagnosed cases of lung cancer seen in various hospital and private laboratories of the Kashmir valley were registered over a period of two years (January 1, 2004 to December 31, 2005). Also included were patients attending the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
5
17
0
Order By: Relevance
“…Inadequate 10 www.pacificejournals.com/apalm eISSN: 2349-6983; pISSN: 2394-6466 [11] In the present study among the 111 primary lung carcinomas studied, the male: female ratio is 3.5:1, with majority of the patients in 6 th decade similar to observations of Koul et al, [12] Sheikh et al [13] Jindal and Behera. [11] There are studies reporting adenocarcinoma in younger age both in men and women.…”
Section: Small Cell Carcinomas 16supporting
confidence: 79%
See 1 more Smart Citation
“…Inadequate 10 www.pacificejournals.com/apalm eISSN: 2349-6983; pISSN: 2394-6466 [11] In the present study among the 111 primary lung carcinomas studied, the male: female ratio is 3.5:1, with majority of the patients in 6 th decade similar to observations of Koul et al, [12] Sheikh et al [13] Jindal and Behera. [11] There are studies reporting adenocarcinoma in younger age both in men and women.…”
Section: Small Cell Carcinomas 16supporting
confidence: 79%
“…The youngest was a 24-year-old male and oldest was an 85-yearold female. Out of 111 cases, adenocarcinomas were 80 (72%) with maximum cases being in the 6th decade and squamous cell carcinomas were 31(28%) with maximum cases being in the 7 th decade (12), with male preponderance seen in both adenocarcinoma (M: F-3:1) and squamous cell carcinoma (M: F-7:1). Initial diagnosis on H&E of adenocarcinoma, 62 cases, and squamous cell carcinoma, 14 cases, were confirmed after IHC.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Lung cancer was reported as the second most common malignancy in an earlier hospital-based study from the Kashmir Valley of the Indian subcontinent. [7] However, a recent study by Koulet al [8] reported that Srinagar, the summer capital of Jammu and Kashmir, has the highest incidence of lung cancer among males in India.…”
Section: Discussionmentioning
confidence: 98%
“…[8,9] Higher prevalence in male is explained by smoking habit, high exposure to atmospheric pollution in outdoor activities in comparison to females but lower sex ratio in our study might be due to increasing incidence of lung cancer in women because of exposure to biomass fuel or other precipitating factors as none of our female patients were smokers. Smoker to non-smoker ratio was high in our study, but is lower to previous Indian studies showing high co-relation between smoking and lung cancer.…”
Section: Discussionmentioning
confidence: 57%